Examining the changes in car ownership levels in the Greater Dublin Area between 2006 and 2011 - CAULFIELD, BRIAN (My University, 2015)
The aim of this study was to examine the changing nature of car ownership in the Greater Dublin Area (GDA) and to determine the character istics of households most likely to have changed their car ownership levels between 2006 a nd 2011. The analysis was carried out using the census data from 2006 and 2011. A multinomial logistic regression model in tandem with geographic information system (GIS) visualisation was used to examine the impact of a set of indi vidual, household and transport characteristics on average car ownership levels. T he findings demonstrate that the age of individuals, the year their household was const ructed, residential density and the mode of travel to work had an impact on the chang e in car ownership levels over the study period. Rail availability had signific ant influence where there was a decrease in average car ownership levels. However , the impact of bus transport on car ownership levels was less apparent. The study was set against the background of the worst economic recession in the history of the Irish state and the impact this had on the findings cannot be ignored. Nonetheless, by identifying househol ds likely to have changed their car ownership over the study period the finding s may assist policymakers in the future as they attempt to create transpor t initiatives which will encourage more sustainable travel modes.
PUBLISHED
Keywords: Car ownership; Smart & Sustainable Planet